Juror decision-making and biracial targets - Yamamoto, Susan; Maeder, Evelyn M. (Frontiers in Cognition, 2024)
Objectives: This study examined potential bias against Biracial defendants using a juror decision-making paradigm. We also tested whether encouraging mock jurors not to endorse racial essentialism (belief that racial groups have inborn, immutable traits that influence behavior) would mitigate bias.Methods: Canadian jury-eligible participants (N = 326) read a fabricated first-degree murder of a police officer case (involving a Black, White, or photo-morphed Black-White Biracial defendant), then made verdict decisions, completed a heuristics questionnaire, and answered racial categorization questions.Results: While there were no significant effects on verdicts, those higher in heuristic thinking tended to estimate a lower percentage of European ancestry for a Biracial defendant when the defense lawyer drew attention to race.Conclusions: Findings suggest that individual differences such as the tendency to rely on heuristic thinking may alter how racially ambiguous targets are perceived.